2018
DOI: 10.1002/jcb.26801
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transient receptor potential channel (TRPC) on airway smooth muscle cell isolated from asthma model mice

Abstract: This study aimed to validate whether transient receptor potential channel1 (TRPC1) and TRPC3 participate in the regulation the proliferation of airway smooth muscle cells (ASMCs) through modulating calcium ion (Ca ) influx in vitro. Chronic model of murine asthma was induced and ASMCs isolated from asthmatic mice were used in this whole study. TRPC1 and TRPC3 were upregulated in asthmatic mouse ASMCs and selected for further investigation. Ca concentration and the cell viability of asthmatic mouse ASMCs were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…TRPC1, one of the TRPC channels, is expressed in almost all tissues and various tumors. Many studies have demonstrated that the TRPC1 channel plays an important role in tumor cell proliferation, differentiation, apoptosis, migration, and invasion in distinct kinds of tumors, including breast cancer, prostate cancer, gastric cancer, and liver cancer (7)(8)(9)(10)(11)(12)(20)(21)(22). The abnormal expression of TRPC1 can accelerate the uncontrolled proliferation and invasion of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPC1, one of the TRPC channels, is expressed in almost all tissues and various tumors. Many studies have demonstrated that the TRPC1 channel plays an important role in tumor cell proliferation, differentiation, apoptosis, migration, and invasion in distinct kinds of tumors, including breast cancer, prostate cancer, gastric cancer, and liver cancer (7)(8)(9)(10)(11)(12)(20)(21)(22). The abnormal expression of TRPC1 can accelerate the uncontrolled proliferation and invasion of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TRPC1 had been extensively studied in various types of tissue or tumor. The abnormal expression of TRPC1 was found to be involved in tumor growth, migration, invasion, and differentiation (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The TRP channels superfamily can be divided into seven subfamilies based on sequence homology: TRPA (ANKTM1), TRPC (canonical), TRPM (melastatin), TRPML (mucolipidins), TRPN (NompC), TRPV (vanil) and TRPP (polycystin) [ 48 ]. Transient receptor potential canonical (TRPC) channels belong to the TRP superfamily and most of them expressed in ASM [ 49 , 50 ]. They may mediated changes in [Ca 2+ ] i and induced ASM abnormal contraction, proliferation, hypertrophy, as well as secretion of inflammatory mediators [ 41 , 51 ].…”
Section: Regulation Of Trp Channels In the Function Of Asmmentioning
confidence: 99%
“…TRPC-1 and TRPC-3 regulate the movement of cations, particularly Ca ++ , across cell membranes to activate Ca ++ -dependent processes. [50][51][52][53] They participate in the formation of store operated calcium channels (SOCC) that maintain cytoplasmic and sarcoplasmic/endoplasmic reticulum Ca ++ balance. Ca ++ channels control the progression of ASM cells through the cell cycle, reducing the levels of phosphorylated p38 mitogen activated protein kinase (p38 MAPK), Jun n-Terminal Kinase (JNK) and Bcl-2, and increase cell survival through decreased caspase 3 cleavage.…”
mentioning
confidence: 99%
“…Ca ++ channels control the progression of ASM cells through the cell cycle, reducing the levels of phosphorylated p38 mitogen activated protein kinase (p38 MAPK), Jun n-Terminal Kinase (JNK) and Bcl-2, and increase cell survival through decreased caspase 3 cleavage. 50 TNF-α and IL-1β modulate inflammatory processes in chronic asthma and during acute exacerbations. IL-1β treatment of human ASM cells enhances the activities of other mediators such as IL-4, IL-5, IL-13, and leukotrienes.…”
mentioning
confidence: 99%